Parâmetros políticos das prioridades na educação pública municipal, no governo da cidade de Vitória (1989-1992) - Costa, Letícia Viana (2006)
This is an analysis of the political parameter of priorities in the municipal public education system, during the administration of the government of the city of Vitória (l989-1992). These priorities are co-substantiated through four axles: the universal access and permanence of the student in school; investments in material resources; buildings and equipments; investment in human resources; qualification and wages; democratization of the administration of the public school, besides quantitative aspects such as the annual allocation for the maintenance and development of teaching and resources invested in municipal education. The theoretical and methodological lens used in order to understand these parameters derive from texts by Antonio Gramsci (1891-1937), as well as considerations presented by intellectuals who interpret him. Gramsci was chosen due to his ample concept of a State and of the leftist political party, as instruments applied to the context of Brazil as a country which is undergoing its redemocratization, as well as the principle of equality, which is basic for the concept of a Unitarian school. The plurality of sources used – primary, secondary and those originating from oral history – has permitted their crossing, as a resource for analysis, and the confirmation of the implementation of a positive policy for the benefit of a more equalitarian standard of education in the municipality of Vitória, between the years of 1989 and 1992.